Meta-analysis of the acute effect of energy drinks on anaerobic performance - Arias Oviedo, Gabriela María (2019)
The consumption of energy drinks (ED) has been increasing in students, active individuals, and athletes due to their probable ergogenic effect. In addition to calories, energy drinks contain caffeine and other ingredients such as taurine, carnitine, and B-complex vitamins. The aim of this study was to examine the effect of ED consumption on anaerobic performance using a meta-analytic approach. A literature search was conducted on five electronic database searchers: PubMed, SPORTDiscus, Springer Link, ProQuest, and Science Direct. Studies that met the inclusion criteria were selected, i.e: experimental studies that assessed anaerobic performance using EDs as a treatment in humans, reporting descriptive statistics, and published in English or Spanish. 15 studies representing 37 effect sizes (ES) with a total of 253 participants (male and female: 21.7±3.7 years old) met the inclusion criteria. Using a random-effects model and a between-group design, an overall 0.123 ES was found (p = 0.009; CI95% = 0.01 to 0.23; Q = 19.5; p= 0.98; I2 = 0.00%). No relationship or difference was found in the moderator variables. In general, the overall ES indicated that there is a significant difference between consuming ED or a placebo for specific anaerobic jump tests.